The Treaty of Waitangi and the Control of Language by R Dawson - Opie, Joss (Victoria University of Wellington Law Review, 2001)
Richard Dawson The Treaty of Waitangi and the Control of Language (Institute of Policy Studies, Wellington, 2001). Paperback, 255 pages, NZ29. This article is a book review of Richard Dawson’s The Treaty of Waitangi and the Control of Language. In his book, Dawson argued that there was a Crown monopoly over the language of the Treaty. Therefore, Dawson called for a balanced dialogue between the Crown and Māori. However, Opie argues that such a binary description of power is problematic and instead adopts Michel Foucault’s bottom-up description of power which allows for a more nuanced view of the respective identities of the Crown and Māori.